The Impact of Corporate Governance Principles on Financial Performance in Jordanian Family Companies - Bouqalieh , Bassam K. (Jordan Journal of Business Administration, 2023)
This study aimed to demonstrate the impact of corporate governance principles on financial performance in Jordanian family companies. The study population consisted of industrial companies listed in the Amman Stock Exchange during the period (2014-2018). Corporate governance was measured by: (the size of the company’s board of directors, the separation of the positions of the chairman and the CEO, the independence of the board members and the percentage of ownership of major shareholders), while the financial performance was measured using financial ratios (profitability and liquidity) and the size of the company and leverage were used as adjusting variables. The study sample consisted of (34) family-owned industrial companies listed in the Amman Stock Exchange out of (51) companies with a percentage of (66.6%) of the total number of industrial companies. The method of multiple-regression analysis was used to determine the effects of the independent variables on the dependent variable, in addition to measuring the degree of interpretation of the independent variables of the variation in the dependent variable. The results of the study showed that there is a statistically significant impact of the implementation of family-business governance (the size of the board of directors, the separation of the positions of the chairman and the CEO, the independence of the members of the board of directors and the percentage of ownership of major shareholders) on the profitability ratio and the liquidity ratio being among the dimensions of financial performance. Corporate-governance variables in the study indicated that 81.4% of family businesses in Jordan apply corporate-governance principles and there was a statistically significant effect of the adjusting variables (company size and leverage) on the profitability and liquidity ratio in family businesses. The study recommended the importance of applying the principles of corporate governance in family companies that have not fully implemented the principles of governance, because of their positive and significant role in enhancing their financial performance